PENINGKATAN HASIL SEMANGKA DI LAHAN KARST MELALUI PRIMING ASAM SALISILAT DAN IRIGASI TETES - Yovi Avianto (AGRICA, 2026)
Watermelon is an important horticultural commodity with increasing production and consumption trends in Indonesia. Its cultivation is now expanding into marginal areas such as karst landscapes, which have low water-retention capacity and thus heighten the risk of drought stress. Adaptive cultivation strategies, including drip irrigation and salicylic acid (SA) seed priming, have the potential to enhance the plant’s physiological resilience. This study aimed to evaluate the combined effects of SA seed priming and irrigation volume on the physiological responses, growth, and yield of watermelon grown under karst conditions. The experiment was conducted from May to July 2025 on Alfisol karst soil in Ponjong, Gunungkidul, using a factorial randomized complete block design with SA seed priming (0, 0.5, 1, and 1.5 mmol L-1) and two drip-irrigation volumes (1.5 and 2.5 L plant-1). Observations included vegetative growth, physiological parameters (photosynthetic rate, transpiration rate, leaf water use efficiency (LWUE), stomatal conductance, and proline content), as well as fruit yield and quality. The results showed that SA and irrigation did not affect vine length or leaf number but increased leaf area and shoot biomass under specific combinations of SA dose and irrigation volume. Physiological traits such as photosynthetic rate, LWUE, and proline were strongly influenced by the interaction of both factors, determining water-use efficiency and plant stress levels. Fruit weight and °Brix increased under optimal SA–irrigation combinations, whereas fruit diameter was affected independently by each factor. Correlation analysis indicated that LWUE and photosynthetic rate were the main determinants of yield and fruit quality, while elevated proline levels were associated with reduced fruit weight.